Targeting colorectal cancer stem cells using curcumin and curcumin analogues: insights into the mechanism of the therapeutic efficacy. Issue 1 (December 2015) - Ramasamy, Thamil; Ayob, Ain; Myint, Hsu; Thiagarajah, Sharmanee; Amini, Farahnaz
Abstract Colorectal cancer is one of the commonest cancers in the world and it is also a common cause of cancer-related death worldwide. Despite advanced treatment strategies, the disease is rarely cured completely due to recurrence. Evidence shows that this is due to a small population of cells, called cancer stem cells (CSCs), in the tumour mass that have the self-renewal and differentiation potential to give rise to a new tumour population. Many pre-clinical and clinical studies have used curcumin and its analogues as anti-cancer agents in various types of cancer, including colorectal cancer. Intriguingly, curcumin and its analogues have also recently been shown to be effective in lowering tumour recurrence by targeting the CSC population, hence inhibiting tumour growth. In this review, we highlight the efficacy of curcumin and its analogues in targeting colorectal CSC and also the underlying molecular mechanism involved. Curcumin, in the presence or absence of other anti-cancer agents, has been shown to reduce the size of tumour mass and growth in both in vivo and in vitro studies by affecting many intracellular events that are associated with cancer progression and CSC formation. An insight into the molecular mechanism has unraveled the mode of action via which curcumin could affect the key regulators in CSC, importantly; (1) the signaling pathways, including Wnt/β-catenin, Sonic Hedgehog, Notch and PI3K/Akt/mTOR, (2) microRNA and (3) the epithelial-mesenchymal transition at multiple levels. Therefore, curcumin could play a role as chemosensitiser whereby the colorectal CSCs are now sensitised towards the anti-cancer therapy, therefore, combination therapy using anti-cancer agent with curcumin could be much more effective than treatment using a single cancer agent. This potential treatment modality can be further developed by employing an effective delivery system using a nanotechnology based approach to treat colorectal cancer.